PPARγ Ameliorates Mycobacterium tuberculosis H37Ra-Induced Foamy Macrophage Formation via the ABCG1-Dependent Cholesterol Efflux Pathway in THP-1 Macrophages - Ye, Yutao; Liu, Jun; Guo, Yang; Gao, Yujie; Rao, Jiayue; Su, Rigu; Zhang, Lu; Huang, Zikun; Luo, Qing; Li, Junming (Frontiers in Microbiology, 2022)
Foamy macrophages are present during the course of Mycobacterium tuberculosis (Mtb) infection and seems to be nutrient-rich reservoir and secure reservoir for the bacilli, which leads to bacterial persistence and infection transmission. Peroxisome proliferator activated receptor γ (PPARγ) is a key transcription factor for cholesterol metabolism in macrophages and its role in regulating atherosclerosis related foamy macrophages (FMs) formation has been well studied. However, knowledge about the mechanism of PPARγ regulating Mtb infection induced FM formation remains very limited. In this study, we investigate the functional role of PPARγ in Mtb H37Ra infection-induced foamy macrophages formation. H37Ra infection induced a time-dependent decreased expression of PPARγ that paralleled the augmented lipid body formation in THP1-derived macrophages. PPARγ antagonist GW9662 significantly potentiate H37Ra induced lipid body formation and inhibit ABCG1 expression, overexpression of ABCG1 by transduced macrophages with lentivirus significantly reversed the promotion effect of GW9662 on FM formation. Moreover, Treatment with a TLR2 neutralizing antibody ameliorated the activation of ABCG1 by Mtb H37Ra without significantly effecting the suppression of PPARγ, suggesting a greater role for TLR2 to regulate ABCG1 compared to PPARγ. Overall, this study showed that PPARγ is involved in ameliorating FM formation by regulating ABCG1 expression, these observations expose a novel role of PPARγ in the Mtb infection induced FM formation.